Dynamic inter-relationships among tourism, economic growth and energy consumption in India. Issue 4 (3rd July 2016) - Tang, Chor Foon; Tiwari, Aviral Kumar; Shahbaz, Muhammad
Abstract: This study attempts to explore the dynamic causal and inter-relationships among tourism, economic growth and energy consumption in India. This study covers the annual data from 1971 to 2012. This study applies the cointegration and generalised variance decomposition methods to verify the relationship. The bounds testing approach to cointegration and the Gregory–Hansen test for cointegration with structural break consistently reveal that energy consumption, tourism and economic growth in India are cointegrated. We find that tourism and economic growth strongly affects energy consumption in the long-run. Additionally, we also find that tourism and economic growth in India are inter-related, but the causal effect of tourism on economic growth is stronger than the other way around in both the short- and long-run. Therefore, this study concludes that the tourism-led growth hypothesis is valid but the energy-led growth hypothesis is invalid in India. With such findings, we can confirm that tourism is an important catalyst of growth to the Indian economy. Therefore, policy-makers should promote and expand tourism industry in order to sustain the process of economic growth and development in India.